The "Middle Way" of John R. Commons: Pursuing Reasonable Value in the Age of Unreason. Issue 4 (1st October 2020) - Whalen, Charles J.
Abstract: John R. Commons sought to orient the U.S. economy in the direction of reasonable value as a way to "save capitalism by making it good." In particular, he offered two paths to that "middle way" between the socio‐political extremes of fascism and communism: judicial sovereignty and collective democracy. This policy note considers a variety of present‐day challenges to pursuit of those paths; some possible ways forward are also suggested.